2016
DOI: 10.1016/j.polymer.2015.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic treatment of polycarbonate/carbon nanotubes composites

Abstract: A twin-screw extruder having an ultrasonic treatment zone in the barrel was used to prepare polycarbonate (PC)/multi-walled carbon nanotubes (MWNTs) composites. The effect of molecular weight of PC, carbon nanotubes (CNTs) concentration and ultrasonic amplitude on processing characteristics, electrical, morphological, rheological and mechanical properties of PC filled with 0.2-1.5 wt% CNTs was investigated. Ultrasonic treatment showed significant effects on improving the dispersion and distribution of CNTs esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
(68 reference statements)
2
21
0
1
Order By: Relevance
“…Figure shows the volume resistivity curve of PC/EPC (10%) blend as a function of MWCNT. The electrical resistivity and percolation threshold of PC/MWCNTs has been reported in previous studies . For the case of PC/MWCNTs nanocomposites, the percolation threshold was reported between 1% and 2% MWCNTs .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Figure shows the volume resistivity curve of PC/EPC (10%) blend as a function of MWCNT. The electrical resistivity and percolation threshold of PC/MWCNTs has been reported in previous studies . For the case of PC/MWCNTs nanocomposites, the percolation threshold was reported between 1% and 2% MWCNTs .…”
Section: Resultssupporting
confidence: 56%
“…The electrical resistivity and percolation threshold of PC/MWCNTs has been reported in previous studies. [53][54][55][56][57][58] For the case of PC/MWCNTs nanocomposites, the percolation threshold was reported between 1% and 2% MWCNTs. 58 The results of the experiment showed that MWCNTs improved the electrical conductivity of the PC/EPC blends.…”
Section: Solubility Parametersmentioning
confidence: 99%
“…Ultrasonic extrusion of polymers has been extensively studied by Isayev and his coworkers. It can be used for devulcanization of rubbers, decrosslinking of crosslinked thermoplastics, compatibilization of polymer blends, and improvement of filler dispersion in polymer composites . The properties of ultrasonically treated polymers are determined by their molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used for devulcanization of rubbers, [5][6][7] decrosslinking of crosslinked thermoplastics, 8 compatibilization of polymer blends, 9,10 and improvement of filler dispersion in polymer composites. [11][12][13][14] The properties of ultrasonically treated polymers are determined by their molecular structures. To better understand the mechanism about how ultrasonic treatment changes the molecular structures of polymers, it is essential to study the effect of ultrasonic treatment on pure polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A elevadas frecuencias o gradiente de cizalla, todas las muestras tienden a converger a los valores del PMMA puro, independientemente de la nanofase añadida, ya que en esas condiciones el comportamiento predominante es el de la matriz del polímero. A valores bajos, sí que existe un incremento de la viscosidad al añadir las diferentes nanofases, especialmente en los nanocomposites procesados a baja SME, ya que en estos casos la movilidad de las cadenas sí que se puede ver fácilmente influenciada [537]. Con respecto al PMMA puro, el incremento máximo de la viscosidad que se produce es de un 26,5% para la nanofase híbrida GO-LI, del 48,6% para la nanofase pura GO y del 62,6% en el caso de la nanofase híbrida que contiene los nanotubos de carbono (GO-NT).…”
Section: Propiedades Reológicasunclassified